Being, humanity, and understanding - Lloyd, G. E. R. (Geoffrey Ernest Richard), 1933- (Oxford : Oxford University Press, 2012)
This cross-cultural study explores the diversity of views that humans have held on being, humanity, and understanding. It asks how far we are bound by the conceptual systems to which we belong, and explores topics such as ontology, morality philosophy of language, and communication.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Ontology; Humanity; Comprehension (Theory of knowledge); Philosophy -- History